2009
DOI: 10.1007/s12665-009-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical characteristics of shallow groundwater in aquifer containing uranyl phosphate minerals, in the Köprübaşı (Manisa) area, Turkey

Abstract: The concentrations of uranium, iron and the major constituents were determined in groundwater samples from aquifer containing uranyl phosphate minerals (meta-autunite, meta-torbernite and torbernite) in the Köprübaşı area. Groundwater samples from wells located at shallow depths (0.5-6 m) show usually near neutral pH values (6.2-7.1) and oxidizing conditions (Eh = 119-275 mV). Electrical conductivity (EC) values of samples are between 87 and 329 lS/cm -1 . They are mostly characterized by mixed cationic Ca dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…causes infiltration problem (Ayers and Westcot 1985). MAR greater than 50 is considered harmful and unsuitable for irrigation purposes (Kacmaz and Nakoman 2010;Islam et al 2016b). About 70% of the studied water falls in this category and remaining 30% falls in suitable category in case of magnesium hazard (Table 4).…”
Section: Magnesium Adsorption Ratio (Mar)mentioning
confidence: 99%
“…causes infiltration problem (Ayers and Westcot 1985). MAR greater than 50 is considered harmful and unsuitable for irrigation purposes (Kacmaz and Nakoman 2010;Islam et al 2016b). About 70% of the studied water falls in this category and remaining 30% falls in suitable category in case of magnesium hazard (Table 4).…”
Section: Magnesium Adsorption Ratio (Mar)mentioning
confidence: 99%
“…Dall'Aglio et al (1974), Murakami et al (1997), and Kaçmaz and Nakoman (2009) have also analyzed waters, which are undersaturated with respect to uranyl phosphates and stated that higher U and P concentrations would be needed for precipitation. However, Murakami et al (1997) showed that uranyl phosphates can form by local saturation at the interfaces of apatite (as P source) and sklodowskite (U source).…”
Section: Comparison Of Model and Observations From Naturementioning
confidence: 99%
“…In this research, the water samples were collected at depths of 260.0-430.0 m (Table 1). MAR values < 50 are considered appropriate for irrigation, but values >50 are considered inappropriate [88]. Considering the designed value of MAR, all the collected samples were in the safe zone and could be used for agricultural purposes.…”
Section: Discussionmentioning
confidence: 99%